Development and application of nanomaterials, nanotechnology and nanomedicine for treating hematological malignancies - Li, Jinxin; Wang, Qiwei; Han, Yingli; Jiang, Lingli; Lu, Siqi; Wang, Beini; Qian, Wenchang; Zhu, Meng; Huang, He; Qian, Pengxu (Journal of hematology and oncology, 2023)
Hematologic malignancies (HMs) pose a serious threat to patients’ health and life, and the five-year overall survival of HMs remains low. The lack of understanding of the pathogenesis and the complex clinical symptoms brings immense challenges to the diagnosis and treatment of HMs. Traditional therapeutic strategies for HMs include radiotherapy, chemotherapy, targeted therapy and hematopoietic stem cell transplantation. Although immunotherapy and cell therapy have made considerable progress in the last decade, nearly half of patients still relapse or suffer from drug resistance. Recently, studies have emerged that nanomaterials, nanotechnology and nanomedicine show great promise in cancer therapy by enhancing drug targeting, reducing toxicity and side effects and boosting the immune response to promote durable immunological memory. In this review, we summarized the strategies of recently developed nanomaterials, nanotechnology and nanomedicines against HMs and then proposed emerging strategies for the future designment of nanomedicines to treat HMs based on urgent clinical needs and technological progress.